An interdisciplinary open access journal - Carlos Alós-Ferrer (Games, 2010)
Over the last fifty years, game theory has evolved from a mathematical theory of optimal behaviour in stylized situations ('games') to a general theory of human behaviour, be it actually observed or normatively desirable. Its scope includes both the mathematical modelling and analysis of competition and conflict and the study of human behaviour in strategic contexts and its determinants. Nowadays, game theory has become the language of economics and is increasingly becoming one of the main methods of analysis in several social sciences. Its theoretical underpinnings can be viewed as a mathematical subdiscipline, while its more behavioural offshoots benefit from cross-fertilization with psychology. Game theory has grown within economics but is, by its very nature, interdisciplinary, to the extent that no game theorist can or should define him or herself in disciplinary terms anymore. Games is a game theory journal, and as such we expect most of its actual content to be related to economics. The scope of the journal, however, is broader. All contributions which foster our understanding of game theory (including decision theory) and its applications are welcome, independently of whether the research methodology is analytic, experimental, or both. We explicitly welcome contributions from economics, mathematics, political science, computer science, psychology, and in general all fields where game theory has become a tool or which can contribute to the understanding of human behaviour in strategic situations.
Keywords: 330